Epidemiology of tick infestation in dogs: prevalence, risk factors and seasonal trends in pakistan - Syed Kashif ABBAS; Mansoor HUSSAIN; Shafi ULLAH; Humaira SHAHEEN; Khalid J. ALZAHRANI; Abid ALI; Haroon AHMED (Kafkas Universitesi Veteriner Fakültesi Dergisi)
Dog ticks are the sever threat to both human and animal life due to their medical importance in transmission of tick borne diseases. The current study aimed to investigate tick infestation, associated risk factors, species diversity and seasonal abundance of ticks in selected regions of Pakistan. A total of 940 dogs (both free roaming and owned) were examined during 2023-24 and 712 tick samples were collected. These ticks were morphologically identified into three species comprising of Rhipicephalus sanguineus (81.5%), Rhipicephalus haemaphysaloides (10.2%) and Rhipicephalus turanicus (8.3%). All demographic and epidemiological information were recorded and chi-square test and logistic regression was performed. Overall prevalence of tick infestation in dogs was 27% (254/940). Infestation rates varied by age groups with highest prevalence observed in puppies <1 year (30.50%). Female dogs showed higher infestation rate (30.60%) compared to male dogs (23.72%). Dogs with short hair had significantly higher infestation rates (31.94%) than long-haired breeds (6.15%) and summer had the highest tick infestation rate (32.42%). The tick prevalence was highest in Gujar Khan while least prevalent in Taxila. Simpson"s Diversity Index (D) and Shannon-Wiener Diversity Index (H") indicated a relatively low and moderate level tick diversity, which highlighted the need for dedicated tick control measures, particularly in regions of high infestation of tick in the dog population.